Subspecies in the global human gut microbiome. Issue 12 (14th December 2017) - Costea, Paul I; Coelho, Luis Pedro; Sunagawa, Shinichi; Munch, Robin; Huerta‐Cepas, Jaime; Forslund, Kristoffer; Hildebrand, Falk; Kushugulova, Almagul; Zeller, Georg; Bork, Peer
Abstract: Population genomics of prokaryotes has been studied in depth in only a small number of primarily pathogenic bacteria, as genome sequences of isolates of diverse origin are lacking for most species. Here, we conducted a large‐scale survey of population structure in prevalent human gut microbial species, sampled from their natural environment, with a culture‐independent metagenomic approach. We examined the variation landscape of 71 species in 2, 144 human fecal metagenomes and found that in 44 of these, accounting for 72% of the total assigned microbial abundance, single‐nucleotide variation clearly indicates the existence of sub‐populations (here termed subspecies). A single subspecies (per species) usually dominates within each host, as expected from ecological theory. At the global scale, geographic distributions of subspecies differ between phyla, with Firmicutes subspecies being significantly more geographically restricted. To investigate the functional significance of the delineated subspecies, we identified genes that consistently distinguish them in a manner that is independent of reference genomes. We further associated these subspecies‐specific genes with properties of the microbial community and the host. For example, two of the three Eubacterium rectale subspecies consistently harbor an accessory pro‐inflammatory flagellum operon that is associated with lower gut community diversity, higher host BMI, and higher blood fasting insulin levels. Using an additional 676 human oral samples, we further demonstrate the existence of niche specialized subspecies in the different parts of the oral cavity. Taken together, we provide evidence for subspecies in the majority of abundant gut prokaryotes, leading to a better functional and ecological understanding of the human gut microbiome in conjunction with its host. Synopsis: Genomic variation within gut microbial species analyzed in > 2, 000 metagenomic samples from three continents reveals strongly structured populations (subspecies) in 44 out of 71 cases. Ecological and functional properties of subspecies as well as associations with the host were explored. For most abundant gut microbes from six phyla, subspecies were detected. Within each host, a single subspecies generally dominates and persists over time. Many subspecies exhibit biogeographic patterning, some Firmicutes subspecies strong restrictions, mostly to Chinese samples. Reconstruction of the subspecies‐specific gene content predicts functional differences, some of which are linked to host health. Abstract : Genomic variation within gut microbial species analyzed in > 2, 000 metagenomic samples from three continents reveals strongly structured populations (subspecies) in 44 out of 71 cases. Ecological and functional properties of subspecies as well as associations with the host were explored.